Educação do campo e saúde: refletindo sobre os parâmetros curriculares nacionais e sua relação com o currículo de uma escola multisseriada do Município de Marapanim, Pará - VIANA, Luana Costa (Universidade Federal do Pará, 2012)
This study was about rural education and health and its research object was the primary education curriculum expressed in the National Curriculum Standarts plus its relation to a multigrade school curriculum from Marapanim city at Pará State. The research opted for a qualitative approach and it was based on documental research as well as field research at Professora Carmen Rabelo Magalhães School. This study analyzed the health conception present in the National Curriculum Standarts, expressed specifically in one of the transversal themes about health, investigating how health and rural environment are understood in these documents, in the textbooks, and in the health conception of teachers, students, parents and guardians. It was done a documental analyze focusing the Education Ministry and the Health Ministry documents, as the Operational Guidelines for Basic Education in Rural schools, the national curriculum standards, the national health policy debates of rural populations and Forest and National Policy Health Promotion, as well as the textbooks adopted in this primary school during 2009 year. It was done an interview with teachers, students, parents, and community leaders involved with the school. The data analysis and the interview result indicated the predominance of single causal conception of health in the National Curriculum Standarts, in the analyzed textbooks, as well among teachers, students and interviewed parents, evidencing a gap on the different aspect of life and health of rural living people.